(untitled) (Research, Society and Development, 2023)
The present study aimed to manufacture active biodegradable films from soy protein isolate (SPI), locust bean gum (LBG) and caruru and blackjack leaf extract. The interaction between the compounds was evaluated through the analysis of FTIR. The effect of extract addition on the microstructure, mechanical properties, antioxidant capacity, UV radiation absorption capacity, color and opacity of the film were evaluated. All extracts interacted with the protein, however only two treatments interacted with the LBG present in the film. Addition of extracts in the film provided an increase in antioxidant activity. The addition of the blackjack extract increased the tensile strength of the films, but reduced their elasticity. The addition of caruru extract, however, not favoring the resistance of the films. All the extracts darkened the films and the caruru extract provided more greenish films than all the other made films. The films containing blackjack extract presented a higher intensity of light absorption in the spectral range of ultraviolet A and C.